Perencanaan Kepegawaian - Cinta Putri Dkrisna; Putri Fadilah; Jericho Leandro; Aris Sujatmiko; Muhammad Reza Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines workforce planning in public sector organizations, addressing key aspects such as recruitment, competency development, placement, and performance evaluation. The primary goal is to improve organizational effectiveness by aligning employee skills with organizational needs. The study employs a literature review methodology, synthesizing findings from relevant journals. Key findings highlight the significance of competency-based planning, enhanced by information technology, to meet the evolving demands of public service delivery. Challenges identified include limited budgets and rigid bureaucracy, impacting effective workforce development. The research contributes by proposing a data-driven and responsive approach to workforce planning to optimize public sector human resource management